Preoperative Stoma Site Marking Decreases Stoma and Peristomal Complications: A Meta-analysis. Issue 3 (May 2020) - Hsu, Mei-Yu; Lin, Jui-Ping; Hsu, Hsiao-Hui; Lai, Hsing-Ling; Wu, Yu-Lin
Abstract : PURPOSE: We systematically reviewed the literature in order to determine whether evidence indicated that preoperative stoma site marking reduces the occurrence of postoperative stoma and peristomal complications. DESIGN: Systematic review with meta-analysis of pooled findings. SUBJECTS/SETTING: We systematically reviewed 6 electronic databases including PubMed, MEDLINE, CINAHL, Cochrane Library for English language articles, along with the Airiti Library and Wanfang Data for Chinese articles for evidence related to the effects of stoma site marking on stoma and peristomal complications. We sought articles published from their inception to January 31, 2018. METHODS: Ten studies that included 2109 participants, each comparing 2 groups of patients who did and did not undergo preoperative stoma site marking, were retrieved and analyzed. RESULTS: In patients who underwent stoma site marking, the marking was associated with reduced stoma and peristomal complications in all stoma types (odds ratio [OR] = 0.52; 95% CI, 0.42-0.64; P < .001). Patients who underwent stoma and had fecal ostomies experienced fewer complications (OR = 0.34; 95% CI, 0.25-0.47; P < .001) than patients with unmarked stomas. In contrast, patients with urostomies did not experience fewer complications when compared to those with unmarked ostomies (OR = 0.531; 95% CI, 0.23-1.21; P = .132). Persons with fecal ostomies also had fewer hernias and peristomal skin complications (ORs = 0.25 and 0.30; 95% CIs, 0.09-0.71 and 0.20-0.44, respectively; both P s < .001). The results revealed that stoma site marking was associated with reduced early and late stoma and peristomal complications (ORs = 0.76 and 0.38; 95% CIs, 0.61-0.94 and 0.32-0.46; P = .010 and P < .001, respectively). CONCLUSIONS: Preoperative stoma site marking is associated with a reduced occurrence of stoma and peristomal complications and should be considered as a standard of preoperative care. Abstract : The CE test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com.